Application of New Type UHF Sensor for Partial Discharge Measurement in Air Insulated Switchgear - Muhammad Kodrat; Jean Pierre Uwiringiyimana; Umar Khayam (Emerging Science Journal, 2026)
Accurate detection of partial discharge (PD) is crucial for monitoring high voltage (HV) and medium voltage (MV) of electrical power assets. Among the various methods used for partial discharge (PD) monitoring, ultra-high-frequency (UHF) monitoring is particularly advantageous for on-site/online applications due to its anti-interference and noise-canceling capabilities. Therefore, this study aimed to focus on the application of an ultrawideband antenna, operating between 0.9 to 4 GHz frequency range, for detecting PD defects in air-insulated switchgear. Specifically, the proposed ultrawideband antenna was designed, optimized, and fabricated on FR4 substrate with a thickness of 1.6 mm and dielectric constant of 4.4. To evaluate the sensitivity performance of the antenna, laboratory experiments were conducted using a PD protrusion model located inside a test chamber. Subsequently, the results were evaluated through waveform analysis, PD power spectrum analysis, scalogram analysis in both the time as well as frequency domains, and finally, the phase-resolved PD (PRPD) pattern analysis. The experimental results show that the proposed UHF antenna could detect PD signals with high sensitivity and high signal-to-noise ratio (SNR) when placed at 120 cm from the source. This implied that the proposed antenna was a suitable sensor for detecting PD in HV and MV air-insulated switchgear.